VARIATION DIFFERENCES OF PHALANX DISTAL FINGER PRINT PATTERN ON KLEPTOMANIA PATIENS AND NON-PATIENTS IN POLICE RESORT JEMBER - Amalia Rozaiza Ightikhoma; Nazaratun Thaiyibah; Ahmad Yudianto (Universitas Muhammadiyah Kalimantan Timur, 2020)
Phalanx distal pattern is a curve appeared and formed an unchangeable pattern unless it is caused by a severe trauma. Phalanx distal patterns are classified into 9, namely, Plain Arch, Tentarch, Ulnar loop, and Accidental. In order to find out suspect’s identity, Indonesia Autometic Print Identification System (INAFIS) used 3 stages, which one of them is to determine pattern variation. Phalanx distal fingerprint on human can be utilized as to identify a person, whereas no one has resembled phalanx distal fingerprint even on twins. In this research, the researcher analyzed tendentious pattern variation of phalanx distal pattern on kleptomaniac in police resort office Jember. Generally, phalanx distal fingerprint pattern found on kleptomaniac tendentiously has unique pattern plain arch as the third most apparent pattern beside unlar loop and whorl, meanwhile it was found radial loop on non-patient as the third most apparent beside unlar loop and whorl which generally was phalanx distal fingerprint.